Epidemiology of Non-Hodgkin’s Lymphoma - Krishna C. Thandra; Adam Barsouk; Kalyan Saginala; Sandeep Anand Padala; Alexander Barsouk; Prashanth Rawla (Medical Sciences, 2021)
Non-Hodgins’s lymphoma (NHL) is the most common hematological malignancy worldwide, accounting for nearly 3% of cancer diagnoses and deaths. NHL is the seventh most prevalent cancer and has the sixth highest mortality among cancers in the US. NHL accounts for 4% of US cancer diagnoses, and incidence has increased 168% since 1975 (while survival has improved 158%). NHL is more common among men, those >65 years old, and those with autoimmune disease or a family history of hematological malignancies. NHL is a heterogenous disease, with each subtype associated with different risk factors. Marginal zone lymphoma (MZL) is strongly associated with Sjogren’s syndrome (SS) and Hashimoto’s thyroiditis, while peripheral T-cell lymphoma (PTCL) is most associated with celiac disease. Occupational exposures among farm workers or painters increases the risk of most of the common subtypes. Prior radiation treatment, obesity, and smoking are most highly associated with diffuse large B-cell lymphoma (DLBCL), while breast implants have been rarely associated with anaplastic large cell lymphoma (ALCL). Infection with Epstein–Barr Virus (EBV) is strongly associated with endemic Burkitts lymphoma. HIV and human herpes virus 8 (HHV-8), is predisposed to several subtypes of DLBCL, and human T-cell lymphoma virus (HTLV-1) is a causative agent of T-cell lymphomas. Obesity and vitamin D deficiency worsen NHL survival. Atopic diseases and alcohol consumption seem to be protective against NHL.